IMPLEMENTASI KEBIJAKAN AFFIRMATIVE ACTION 30% KUOTA DALAM KETERWAKILAN PEREMPUAN DI DPRD KOTA TASIKMALAYA TAHUN 2019 - Irawati Irawati; Siti Nuraini (Governance, 2024)
This reserach aims to analyze how the 30% women’s affirmative action policy impact women’s representation in the Tasikmalaya City DPRD and explain the factors that hinder the 30% women’s representation policy in the 2019 legislative elections. This research is motivated by the case of the decline in women’s representation in 2019, namely only reached 6.7 %. With this relatively small number, it is a concern for the Tasikmalaya city government to make more efforts regarding the empowerment of women in thei participation in the political field, especiallyin legislative institutions. This research uses a qualitative method with a descriptive approach. Data collection was carried out using literature study techniques and field studies through observation and interviews. The data source comes from 4 party management members consisting of the Golkar, Gerindra, PDI Perjuangan, and PPP parties, then 2 of them and the KPUD commisioner and a female member of the DPRD council. The results of this research show that the affirmative action policy with a minimum quota of 30% of women in the legislative election nomination stagehas been fulfilled by political parties. This can be seen from the placement of women’s representation in each electoral district in Tasikmalaya city. However, this fulfillment has not yet had a significant impact on increasing women’s representation in Tasikmalaya City DPRD seats, this is caused by several factors that occur, including economic limitations, social contruction, and also party networking. Political is still not optimal for increasing women representation.